1993
DOI: 10.1042/bj2900743
|View full text |Cite
|
Sign up to set email alerts
|

The structural basis of the inhibition of human α-mannosidases by azafuranose analogues of mannose

Abstract: Eight pyrrolidine, five pyrrolizidine and one indolizidine analogue(s) of the known alpha-mannosidase inhibitor, the azafuranose, 1,4-dideoxy-1,4-imino-D-mannitol (DIM), have been tested for inhibition of the multiple forms of alpha-mannosidase in human liver in vitro. Substitution of the ring nitrogen markedly decreased or abolished inhibition, but loss of the C-6 hydroxy group, as in 6-deoxy-DIM and 6-deoxy-6-fluoro-DIM, enhanced inhibition, particularly of the lysosomal alpha-mannosidase. Addition of the an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
33
0
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(34 citation statements)
references
References 29 publications
0
33
0
1
Order By: Relevance
“…For example, the five-membered ring isomer of DMJ is a potent class II a-d-mannosidase inhibitor. [8] Therefore, it is not generally straightforward to predict by an entirely logical design based upon configurational analogy the structure of the best inhibitor for a given carbohydrate-processing enzyme.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the five-membered ring isomer of DMJ is a potent class II a-d-mannosidase inhibitor. [8] Therefore, it is not generally straightforward to predict by an entirely logical design based upon configurational analogy the structure of the best inhibitor for a given carbohydrate-processing enzyme.…”
Section: Introductionmentioning
confidence: 99%
“…[7b] In addition, in certain cases, five-membered ring aza-sugars have been shown to give rise to higher inhibition than their six-membered ring counterparts [8] and subtle selectivities may be observed for five-versus sixmembered ring systems. For example, the five-membered ring isomer of DMJ is a potent class II a-d-mannosidase inhibitor.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, it has been reported that australine analogues, that have the same configuration at C-7a, also inhibited human a-mannosidases. [23] Next, K i and type of inhibition were determined for the active compounds (Table 2, and the LineweaverBurke plots in Figure 1, see the Dixon plots in the Supporting information). Compound 6, K i = 4.7 mM, is a rather potent competitive inhibitor of a-d-glucosidase from rice, indicating that it would mimic the substrate and interact with the enzyme active site.…”
mentioning
confidence: 99%
“…[17][18][19] On the other hand, to the best of our knowledge the potency and selectivity of five-and six-member ring compounds containing endocyclic oxygen, such as derivatives of D-lyxose and D-mannose, have not been investigated in detail. These carbohydrate cores possess cis-configured OH groups at positions 2 and 3, which are necessary for binding to Zn 2+ co-factor at the active site of dGMII.…”
Section: Introductionmentioning
confidence: 97%